Clinical severity and cardiac phenotype in phosphomannomutase 2-congenital disorders of glycosylation : Insights into genetics and management recommendations - Holubova, Veronika; Barone, Rita; Grunewald, Stephanie; Tesařová, Markéta; Hansíková, Hana; Augustínová, Jana; Sykut-Cegielska, Jolanta; De Nictolis, Francesca; Diaz-Moreno, Unai; Elangovan, Ramyia; Epifani, Florencia; Gasperini, Serena; et al. (Journal of inherited metabolic disease, 2025)
Cardiac involvement (CI) in phosphomannomutase 2-congenital disorders of glycosylation (PMM2-CDG) is part of the multisystemic presentation contributing to high mortality rates. The most common cardiac manifestations are pericardial effusion, cardiomyopathy, and structural heart defects. A genotype-phenotype correlation with organ involvement has not yet been described. We analyzed clinical, biochemical, and molecular genetic data of 222 patients from eight European centers and characterized the natural course of patients with CI. Fifty-seven patients (45 children) presented with CI, of whom 24 died (median age 21 months, standard deviation 49.8). Pericardial effusion was the most frequent manifestation (55.4%), occurring mostly within the first 6 months of life. The most common pathogenic variants in patients with CI were p.(Arg141His) in 74%, followed by p.(Val231Met) in 36%, which is 3.5 times higher than in PMM2-CDG patients without CI (p < 0.0001). Twenty-one out of 36 patients with p.(Val231Met) had CI; among them, 15 died, compared to 33 out of 166 patients without p.(Val231Met) who had CI (p < 0.0001). Nine out of 33 patients died (p = 0.0015), indicating greater clinical severity. Furthermore, the p.(Val231Met) variant is predominant in Eastern Europe, suggesting a founder effect. Cardiac complications in PMM2-CDG patients are common and serious. The variant p.(Val231Met) profoundly influences the extent of CI and mortality rates. Therefore, we recommend cardiac surveillance be included in the follow-up protocols for PMM2-CDG.
Keywords: Male; Infant; Evropa; Child; Europe; genetické asociační studie; předškolní dítě; stupeň závažnosti nemoci; Mutation; Phenotype; Humans; Child, Preschool; vrozené poruchy glykosylace; Phosphotransferases (Phosphomutases); novorozenec; mužské pohlaví; Female; mladiství; Cardiomyopathies; ženské pohlaví; kojenec; Genetic Association Studies; Severity of Illness Index; kardiomyopatie; Congenital Disorders of Glycosylation; Adolescent; mutace; lidé; dítě; fenotyp; Infant, Newborn; fosfotransferasy (fosfomutasy)